Partner-directed gaze and co-speech hand gestures: effects of age, hearing loss and noise - Kim, Jeesun; Hazan, Valerie; Tuomainen, Outi; Davis, Chris (Frontiers in Psychology, 2024)
Research on the adaptations talkers make to different communication conditions during interactive conversations has primarily focused on speech signals. We extended this type of investigation to two other important communicative signals, i.e., partner-directed gaze and iconic co-speech hand gestures with the aim of determining if the adaptations made by older adults differ from younger adults across communication conditions. We recruited 57 pairs of participants, comprising 57 primary talkers and 57 secondary ones. Primary talkers consisted of three groups: 19 older adults with mild Hearing Loss (older adult-HL); 17 older adults with Normal Hearing (older adult-NH); and 21 younger adults. The DiapixUK “spot the difference” conversation-based task was used to elicit conversions in participant pairs. One easy (No Barrier: NB) and three difficult communication conditions were tested. The three conditions consisted of two in which the primary talker could hear clearly, but the secondary talkers could not, due to multi-talker babble noise (BAB1) or a less familiar hearing loss simulation (HLS), and a condition in which both the primary and secondary talkers heard each other in babble noise (BAB2). For primary talkers, we measured mean number of partner-directed gazes; mean total gaze duration; and the mean number of co-speech hand gestures. We found a robust effects of communication condition that interacted with participant group. Effects of age were found for both gaze and gesture in BAB1, i.e., older adult-NH looked and gestured less than younger adults did when the secondary talker experienced babble noise. For hearing status, a difference in gaze between older adult-NH and older adult-HL was found for the BAB1 condition; for gesture this difference was significant in all three difficult communication conditions (older adult-HL gazed and gestured more). We propose the age effect may be due to a decline in older adult’s attention to cues signaling how well a conversation is progressing. To explain the hearing status effect, we suggest that older adult’s attentional decline is offset by hearing loss because these participants have learned to pay greater attention to visual cues for understanding speech.